The Family of Ibn-Abi-Zakri Kurdish and its Political and Military Role During the Ayyubid and Mamluk Times - Al Atroshy, Shawkat Shawkat; Hassan, Darwish Y. (Humanities Journal of University of Zakho, 2017)
This paper deals with the history of a well-known Kurdish family in the Ayyubid period. This family is referred to in historical sources as (IbnAbiZekri). The members of this family played a very important military and political role in Egypt and Syria in the Ayyubid period and the first Memluki period. The paper is divided into two sections. The first section traces the origin of this family and its relations with the Ayyubid, its most important emirs and their roles in political events. The second section tackles their stance toward the Crusaders and the Mongol invasion. It also deals with their role in administrating cities and Hajj. The members of this family provided generous support for scholars and men of letters and attracted a large number of them to their court in Syria and Egypt and helped in enhancing cultural relations between Islamic regions.